An Investigation of Regional Plantar Soft Tissue Hardness and Its Potential Correlation with Plantar Pressure Distribution in Healthy Adults. (12th June 2021) - Helili, Maimaitirexiati; Geng, Xiang; Ma, Xin; Chen, Wenming; Zhang, Chao; Huang, Jiazhang; Wang, Xu
Abstract : Background . The plantar soft tissue plays a critical role in absorbing shocks and attenuating excessive stresses during walking. Plantar soft tissue property and plantar pressure are critical information for footwear design and clinical assessment. The aim of this study was to investigate the relationship between plantar soft tissue hardness and plantar pressure during walking. Methods . 59 healthy volunteers (27 males and 32 females, aged 20 to 82) participated in this study. The plantar surface was divided into five regions: lateral rearfoot, medial rearfoot, lateral midfoot, lateral forefoot, and medial forefoot, and the plantar tissue hardness was tested using Shore durometer in each region. Average dynamic pressures in each region were analyzed for the five regions corresponding to the hardness tests. The relationship between hardness and average dynamic pressure was analyzed in each region. Results . The average hardness of the plantar soft tissue in the above five regions is as follows: lateral rearfoot (34.49 ± 6.77 ), medial rearfoot (34.47 ± 6.64 ), lateral midfoot (27.95 ± 6.13 ), lateral forefoot (29.72 ± 5.47 ), and medial forefoot (28.58 ± 4.41 ). Differences of hardness were observed between age groups, and hardness of plantar soft tissues in forefoot regions increased with age (P < 0.05 ). A negative relationship was found between plantar soft tissue hardness and pressure reduction at lateral rearfoot, medial rearfoot, and lateral midfoot (P < 0.05 ). Conclusion . The hardness of plantar soft tissues changes with age in healthy individuals, and there is a trend of increasing hardness of the plantar soft tissue with age. The plantar soft tissue hardness increases with plantar pressure.